Efficacy of Ginger and Neem Plant Extracts against Nematode Parasites in Local Chickens: A Comparative Study: Evaluasi Khasiat Ekstrak Tanaman Jahe dan Mimba terhadap Parasit Nematoda pada Ayam Lokal: Studi Perbandingan - Rasha Shamil Hussein; Omaima Ibrahim Mahmoud (Academia Open, 2023)
This research, conducted from May 2022 to February 2023, aimed to assess the effectiveness of alcoholic and aqueous extracts from Zingiber officinale (ginger) and Azadirachta indica (neem) plants against nematode parasites in local chickens within Salah al-Din, Iraq. A total of 360 chicken fecal samples were collected from various areas and examined using light microscopy, identifying Tichostrongylus tenius and Subulura brumpti as the prevalent nematode species. The study revealed that the 100% concentration of alcoholic neem extract exhibited the highest efficacy, eliminating worms within hours compared to the control group. Ginger extracts also demonstrated effectiveness, with the 100% concentration displaying rapid worm elimination. The results suggest the potential use of these plant extracts as natural remedies for nematode infestations in poultry, addressing critical health and economic concerns in the industry. Highlights : Alcoholic neem extract at 100% concentration showed rapid efficacy against nematode parasites. Ginger extracts also demonstrated effectiveness in eliminating parasites. Potential for using plant extracts as natural remedies in poultry farming. Keywords : Nematode parasites, Ginger extract, Neem extract, Poultry health, Natural remedies